Improvement of Organizational Citizenship Behavior (OCB) through Strengthening Organizational Culture, Teamwork, Personality, and Decision Making - Octavita, Rr.Astri Indriana; Kadar, Isman; Retnowati, Rita (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The purpose of the research is to produce strategies and ways to improve the Organizational Citizenship Behaviour (OCB) of private vocational school teachers, namely by strengthening the independent variables that have a positive effect on teacher OCB. These variables are Organizational Culture, Teamwork, Personality, and Decision Making. The optimal solution found is then used as a recommendation to related parties, namely teachers, principals, school supervisors, school management institutions and education agencies. The method used in this research is quantitative research using survey methods and path analysis techniques and SITOREM analysis to analyze indicators to determine optimal solutions in improving teacher OCB. The research was conducted on permanent foundation teachers (GTY) of private Vocational High Schools (SMK) in East Jakarta with a population of 381 teachers, with a sample of 195 teachers calculated using the Taro Yamane formula. The results of this study are that there is a positive direct effect of organizational culture, teamwork, personality, and decision making variables on OCB; there is a positive direct effect of organizational culture, teamwork, and personality on OCB; there is a positive indirect effect of organizational culture, teamwork, and personality on OCB through decision making.